Genetic Factors for Ischemic and Hemorrhagic Stroke in Japanese Individuals - Yamada, Yoshiji; Metoki, Norifumi; Yoshida, Hidemi; Satoh, Kei; Kato, Kimihiko; Hibino, Takeshi; Yokoi, Kiyoshi; Watanabe, Sachiro; Ichihara, Sahoko; Aoyagi, Yukitoshi; Yasunaga, Akitomo; Park, Hyuntae; et al. (Stroke (1970), 2008)
Background and Purpose— Although genetic epidemiologic studies have implicated several genetic variants as risk factors for ischemic or hemorrhagic stroke, the genetic determinants of these conditions remain largely unknown. We performed an association study to identify gene polymorphisms that confer susceptibility to atherothrombotic cerebral infarction, intracerebral hemorrhage, or subarachnoid hemorrhage. Methods— The study population comprised 3432 unrelated Japanese individuals: 1362 stroke patients (822 with atherothrombotic cerebral infarction, 333 with intracerebral hemorrhage, and 207 with subarachnoid hemorrhage) and 2070 controls. The genotypes for 50 polymorphisms of 38 candidate genes were determined by a method that combines the polymerase chain reaction and sequence-specific oligonucleotide probes with suspension array technology. Results— An initial χ 2 test (false discovery rate <0.05) and subsequent multivariable logistic-regression analysis with adjustment for conventional risk factors ( P <0.05) revealed that the −14C→T polymorphism (rs1800977) of ABCA1 , the A→C (rs3027898) and C→T (Ser532Leu, rs1059703) polymorphisms of IRAK1 , and the G→C (Cys2229Ser) polymorphism (rs619203) of ROS1 were significantly associated with atherothrombotic cerebral infarction; that the −428G→A polymorphism (rs710968) of LIMK1 was significantly associated with intracerebral hemorrhage; and that the 13989A→G (Ile118Val) polymorphism (NC_000007.12) of CYP3A4 was significantly associated with subarachnoid hemorrhage. Conclusions— Genotypes for ABCA1 , IRAK1 , and ROS1 may prove useful for assessment of the genetic risk for atherothrombotic cerebral infarction, whereas those for LIMK1 and CYP3A4 may be similarly beneficial in assessment of the genetic risk for intracerebral hemorrhage and subarachnoid hemorrhage, respectively. Validation of these findings will require additional studies with independent subject panels.